Strategy of multinational corporations in the XXI century (Путеводитель предпринимателя, 2020)
In article major factors and forms of actions of multinational corporations in the global markets, and also problems and ways of «exit» to these markets of new firms, including Russian, and consequences of these processes for national, especially transitional, economy are considered, in particular, at formation of innovative potential.